1988
DOI: 10.1042/bj2500827
|View full text |Cite
|
Sign up to set email alerts
|

The iron(III)-adriamycin complex inhibits cytochrome c oxidase before its inactivation

Abstract: Cytochrome c oxidase was found to be competitively inhibited by a complex formed between Fe3+ and the cardiotoxic antitumour drug adriamycin (doxorubicin) with an inhibition constant, Ki, of 12 microM. This competitive inhibition precedes the slower Fe3+-adriamycin induced inactivation of cytochrome c oxidase. In strong contrast with this result, free adriamycin was not observed to either inhibit or inactivate cytochrome c oxidase (Ki greater than 3 mM). Since, typically, polycations are known to inhibit cytoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…It may facilitate A␤ oligomerization (Atwood et al, 1998;Klug et al, 2003), may facilitate the formation of specific A␤ conformers such as dityrosine A␤ (Galeazzi et al, 1999;Curtain et al, 2001;Atwood et al, 2004), or may facilitate A␤-COX interaction, serving as a ligand. A precedent for the latter scenario may be the adriamycin/Fe 3ϩ -mediated inhibition of COX observed by Hasinoff and Davey (1988). These authors found that adriamycin inhibited COX with an inhibition constant of 12 M when in the presence of Fe 3ϩ , and this inhibition was lost when the metal was removed by chelators.…”
Section: Discussionmentioning
confidence: 87%
“…It may facilitate A␤ oligomerization (Atwood et al, 1998;Klug et al, 2003), may facilitate the formation of specific A␤ conformers such as dityrosine A␤ (Galeazzi et al, 1999;Curtain et al, 2001;Atwood et al, 2004), or may facilitate A␤-COX interaction, serving as a ligand. A precedent for the latter scenario may be the adriamycin/Fe 3ϩ -mediated inhibition of COX observed by Hasinoff and Davey (1988). These authors found that adriamycin inhibited COX with an inhibition constant of 12 M when in the presence of Fe 3ϩ , and this inhibition was lost when the metal was removed by chelators.…”
Section: Discussionmentioning
confidence: 87%
“…There is evidence suggesting that the Dox treatment can induce apoptosis by multiple different mechanisms (Mukhopadhyay et al, 2009). Moreover, Dox causes iron dysregulation by the formation of Fe 3+ -Dox complex leading to inactivation of cytochrome c oxidase (Hasinoff & Davey, 1988), and changes in iron homeostatic processes associated with aconitase-iron regulatory protein-1 (ACO1) (Minotti et al, 1998).…”
Section: +mentioning
confidence: 99%
“…Galactosylsphingosine as well was observed (Igisu & Nakamura, 1986) to inhibit cytochrome c oxidase strongly (Ki -5 tM). In previous studies cytochrome c oxidase kinetics exhibited weak inhibition by pentan-I -ol, propan-1 -ol, propan-2-ol, methanol, glycerol and sucrose (Hasinoff & Davey, 1987, 1988. It has been shown by Orii & Yoshikawa (1973) that hydroxylamine, hydrazine, semicarbazide, salicylaldoxime and ethylxanthate inhibit cytochrome c oxidase with inhibition constants as low as 0.5 ,uM.…”
Section: Introductionmentioning
confidence: 99%